2011
DOI: 10.1105/tpc.111.083030
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin Mediates Endocytosis and Polar Distribution of PIN Auxin Transporters inArabidopsis 

Abstract: Endocytosis is a crucial mechanism by which eukaryotic cells internalize extracellular and plasma membrane material, and it is required for a multitude of cellular and developmental processes in unicellular and multicellular organisms. In animals and yeast, the best characterized pathway for endocytosis depends on the function of the vesicle coat protein clathrin. Clathrin-mediated endocytosis has recently been demonstrated also in plant cells, but its physiological and developmental roles remain unclear. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
338
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(356 citation statements)
references
References 70 publications
(119 reference statements)
18
338
0
Order By: Relevance
“…To test this hypothesis, we examined AMT1;3 internalization in the chc2 mutants, which are defective in bulk endocytosis, as well as in internalization of prominent plasma membrane proteins (25). In chc2, we found that the internalization of AMT1;3-EGFP spots in N-sufficient conditions was inhibited and the spots amassed into clusters with larger spot size and higher fluorescence intensity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we examined AMT1;3 internalization in the chc2 mutants, which are defective in bulk endocytosis, as well as in internalization of prominent plasma membrane proteins (25). In chc2, we found that the internalization of AMT1;3-EGFP spots in N-sufficient conditions was inhibited and the spots amassed into clusters with larger spot size and higher fluorescence intensity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The polar localization of PIN proteins at the apico-basal domain of root cells requires clearance from the PM by endocytosis involving clathrin (37,38), retargeting to and retention at the polar domain (39,40). Similarly, possible tyrosine-based motifs have been involved in the lateral polarity of BOR1, suggesting a role for endocytosis that depends on clathrin in this process (27).…”
Section: Resultsmentioning
confidence: 99%
“…Both clathrindependent and -independent internalization mechanisms have been described in plants (23,24). Because clathrin has been shown to function in BRI1 endocytosis (9), we addressed genetically whether clathrin is required for the internalization of PRRs.…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis, two related genes, CHC1 and CHC2, encode clathrin heavy chains, of which chc2 mutants were shown to affect endocytic events from the plasma membrane (23). To investigate whether FLS2 endocytosis is mediated by CHC2 in Arabidopsis, we treated cotyledons of chc2-1 mutants with TAMRA-flg22.…”
Section: Resultsmentioning
confidence: 99%